(untitled) (Research, Society and Development, 2021)
The Acquired Human Immunodeficiency Syndrome (AIDS) burdens society and represents one of the greatest challenges of global health due to the severity, dissemination and inequality in access to antiretroviral therapy. Objective: to analyze the thickness of the bone trabeculae and the total collagen density of fragments from bone marrow autopsies with AIDS deficiency. Methodology: retrospective observational, analytical and quantitative study, carried out from 60 bone marrow fragments from autopsied patients, aged between 26 and 71 years, divided into four groups, adults and elderly with and without AIDS. For the histomorphometric analysis, histomorphometric techniques with common light microscopy were used for quantitative analysis of the thickness and microscopy technique with polarized light to evaluate the total collagen in the bone trabeculae. Results: Adult and elderly groups with dissipation AIDS decreased in trabecular bone thickness compared to groups of adults and elderly without AIDS (p<0.001). In the assessment of collagen in groups of adults and elderly people with AIDS, there was a significant increase in total collagen (p<0.001) compared to groups without AIDS. When comparing adults and elderly people with AIDS, there was a significant increase in total collagen in the adult group (p = 0.041). As a complementary result, the body mass index among the groups with AIDS decreased, decreasing in the elderly group (p = 0.040) compared to the adult group. Conclusion: the AIDS factor influences the decrease in the thickness of the bone trabeculae and favors the increase in total collagen in adults and the elderly, being an important factor in the assessment of bone mass, especially in those aged over 50 years who present the greatest loss of organic matrix.